Properties of 3-(1-Phenyl-Propyl)-4-Oxycoumarin (Marcoumar®) in the Plasma when Tested in Normal Cases and under the Influence of Drugs - Seiler, K; Duckert, F (Thrombosis and Haemostasis, 1968)
A fluorimetric method served to determine Marcoumar in blood plasma. The biological half-time of Marcoumar after an administration of 2.2 mg/10 kg is 6½ days. Variations in maintenance dose requirements seem not to be primarly determined by differences in absorption or excretion of the anticoagulant drug. In therapeutical concentrations about 99% of the drug are bound to plasma protein. Marcoumar can be displaced in vitro from plasma protein by different drugs. The anticoagulant effect is not increased in every case in which the anticoagulant is displaced in plasma from its protein binding.